2011
DOI: 10.2308/isys-10091
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Consumer Information Privacy from the Accounting Information Systems Perspective

Abstract: The information privacy of consumers is an important public policy issue in today's society, and one that businesses, industries, and governments are continuing to struggle with as information technology (IT) innovations create ever-stronger impacts. In this article, we explore consumer information privacy issues and review the results of related prior research. We provide a survey of the literature on information privacy based on our assessment from: (1) the societal and public policy perspective, (2) the bus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 99 publications
(133 reference statements)
1
15
0
2
Order By: Relevance
“…Although some of our discussion may apply to broader enterprise information privacy concerns (i.e., non-e-commerce settings), we limit the scope of our review in this paper solely to privacy in an e-commerce setting. A paper by Kauffman et al (2011) addresses research on the broader information privacy issues.…”
Section: Introductionmentioning
confidence: 99%
“…Although some of our discussion may apply to broader enterprise information privacy concerns (i.e., non-e-commerce settings), we limit the scope of our review in this paper solely to privacy in an e-commerce setting. A paper by Kauffman et al (2011) addresses research on the broader information privacy issues.…”
Section: Introductionmentioning
confidence: 99%
“…Given recent research that calls for studies in the area of privacy, including consumer attitudes and beliefs regarding privacy, the present study proposes and validates a conceptual model that weighs the relative importance of different types of consumer privacy concerns related to location-based services on behavioral intentions (Kauffman, Lee, Prosch, and Steinbart 2011). The resultant findings indicate the importance of unraveling the intricacies related to the specific components of privacy concerns and their relative weight on consumer intentions to disclose.…”
Section: Discussionmentioning
confidence: 69%
“…Privacy is an important ongoing public policy and research area (Kauffman et al 2011). U.S. courts have long indicated that emails that reside on the company's computers belong to the company and that employees generally have no privacy protection (Gubins 2008;Smith and Tabak 2009).…”
Section: Ro13: Exploring the Privacy And Policy Issues Associated Witmentioning
confidence: 99%